ANALYSIS OF CERVICAL CANCER PREVENTIVE BEHAVIORS IN WOMEN OF FERTILIZING AGE BASED ON HEALTH PROMOTION MODEL THEORY IN NGANJUK DISTRICT - Eka Pujiastutik, Yanuar; Wahyuni, Sri; Sholeh Apriyanto, Bagus (Universitas Airlangga, 2026)
Introduction: Behavioral actions of women of reproductive age (WRA) regarding the prevention of cervical cancer are very necessary to change women's attitudes and behavior in maintaining reproductive health. The aim of this research is to analyze the prevention of cervical cancer behavior in women of childbearing age based on the Health Promotion Model Theory. Method: This study employed an analytical quantitative observational approach. It involved sampling all women of childbearing age in Sumengko Village, Sukomoro District, Nganjuk Regency, resulting in a total of 96 respondents. The independent variables examined in this study included several causal factors: age, education, employment, perceived benefits of action, perceived barriers to action, self-efficacy, attitudes toward activities, interpersonal influence, and situational influence. The dependent variable was preventive behavior regarding cervical cancer. Questionnaires were used as the instruments for data collection, which were then analyzed using a logistic regression test. Result: The research results show that there is a significant relationship between situational influence and cervical cancer preventive behavior (p = 0.00 ≤ α = 0.05). Meanwhile, there is no relationship between age, education, employment, perceived benefits of action, perceived barriers, self-efficacy, attitude toward activities, and interpersonal influence with cervical cancer preventive behavior. Conclusion: It was concluded that there was a significant relationship between situational influences and cervical cancer preventive behavior. Strengthening supportive environments and situational factors is recommended to enhance women’s cervical cancer preventive behaviors. Keywords: Health Promotion Model Theory, cervical cancer, preventive behavior, women of reproductive age (WRA)